Global response sensitivity analysis of uncertain structures. (January 2016) - Greegar, G.; Manohar, C.S.
Highlights: Development of global response sensitivity indices based on model distance measures. Treatment of probabilistic and non-probabilistic input variables in defining the indices. Examination of merits in employing Kantorovich distance measures in defining the indices. Abstract: The problem of characterizing global sensitivity indices of structural response when system uncertainties are represented using probabilistic and (or) non-probabilistic modeling frameworks (which include intervals, convex functions, and fuzzy variables) is considered. These indices are characterized in terms of distance measures between a fiducial model in which uncertainties in all the pertinent variables are taken into account and a family of hypothetical models in which uncertainty in one or more selected variables are suppressed. The distance measures considered include various probability distance measures (Hellinger, l 2, and the Kantorovich metrics, and the Kullback–Leibler divergence) and Hausdorff distance measure as applied to intervals and fuzzy variables. Illustrations include studies on an uncertainly parametered building frame carrying uncertain loads.